2021
DOI: 10.21037/apm-21-1822
|View full text |Cite
|
Sign up to set email alerts
|

Cranioplasty for patients with disorders of consciousness

Abstract: Background: Cranioplasty (CP) is necessary for patients with disorders of consciousness (DOC) and skull defects. However, due to the complexity of these conditions, the surgical indications are conservative, and there are few published reports. This study aimed to assess the outcomes and complications of CP in patients with DOC, and to optimize the management of transcalvarial herniation (TCH) and hydrocephalus.Methods: A total of 87 patients with DOC who underwent CP at our center between December 2016 and Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“… 21 , 33 However, VPS before DC may be associated with VPS hyper drainage, and VPS before or contemporary to CP may be associated with an increased risk of neurosurgical complications. 38 In our series, our interviewees reported that VPS was performed before CP in 15.9% of cases, a value similar to that (13.8%) reported by Dang et al 38 Also, our survey reported severe complications in 50% of the cases, thus explaining the strong disagreement with large ES between the ICC statement indicating the opportunity to perform VPS after CP in the case of hydrocephalus and the neurorehabilitation physicians’ perception of the actual practice. Considering this evidence, in patients with DC in whom the development of HC is suspected, CP should be performed as soon as possible in the absence of contraindications.…”
Section: Discussionsupporting
confidence: 82%
“… 21 , 33 However, VPS before DC may be associated with VPS hyper drainage, and VPS before or contemporary to CP may be associated with an increased risk of neurosurgical complications. 38 In our series, our interviewees reported that VPS was performed before CP in 15.9% of cases, a value similar to that (13.8%) reported by Dang et al 38 Also, our survey reported severe complications in 50% of the cases, thus explaining the strong disagreement with large ES between the ICC statement indicating the opportunity to perform VPS after CP in the case of hydrocephalus and the neurorehabilitation physicians’ perception of the actual practice. Considering this evidence, in patients with DC in whom the development of HC is suspected, CP should be performed as soon as possible in the absence of contraindications.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, early CP was found to improve cognitive function by restoring CSF hydrodynamics, intracranial compliance, and cerebral blood flow when neurocognitive changes are at their peak [26]. However, when is the right timing to perform CP is still controversial because it variably affects functional recovery and is also a risk factor for infections and other complications [32,33]. Archavlis et al [34], in a 10-year retrospective study on a cohort of 200 patients, observed that patients who performed CP within 7 weeks from the decompressive craniectomy had an improvement of 78% (measured by the GCS) versus the 46% observed in patients who underwent cranioplasty after 7-12 weeks and only 12% after 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…5 , 8 Some patients with MCS may even gradually regain consciousness and motor functions after effective rehabilitation and eventually return to society. 9 …”
Section: Introductionmentioning
confidence: 99%
“…They are more responsive to stimuli, such as auditory stimuli and electrical stimulation, 6,7 show greater activation of cortical metabolic rates, and are more likely to regain consciousness with natural recovery or rehabilitation due to preservation of their brain function 5,8 . Some patients with MCS may even gradually regain consciousness and motor functions after effective rehabilitation and eventually return to society 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation